The Effect of Non- Ioic Surfactant in Gravity Drainage Processes in the Reservoir to Increase Oil Production at a Laboratory Scale - Nanda Josenia Sainuka; Sugiatmo Kasmungin; Dwi Atty Mardiana (Penerbitan Universitas Trisakti, 2021)
Chemical flooding is one of the methods used to increase oil recovery. One of the chemical flooding used is alkaline surfactant, where the alkaline and surfactant function is to reduce interface stress and form microemulsion . In this study, a screening of surfactant was conducted in order to determine which surfactants were compatible and then injected to increase oil production. The surfactants used in this study were non-ionic surfactants namely Poly Ethylene Glycol Monooleate (PEGM), Nonyl Phenol Ethoxylate (NP-6), Poly Ethylene Glycol Diolate (PD) and Sodium Dodecyl Benzene (SDB) with surfactant concentrations of 0.3 %, NaCL concentrations of 0%, 2% and 5%, and alkaline concentrations (NaOH and Na2CO3) of 0.05%, 0.1% and 0.5%. The result obtained from the measurement of Interfacial Tension (IFT) surfactant PEGM 3% at the brine concentration of 2% was 0.012638 Dyne/cm. After that imbibition testing was performed to perceive the ability of surfactants to bind oil in rock pores, the highest oil recovery was 75.7% in PEGM surfactant concentration of 0.3%, salinity of 2%, and NaOH alkaline of 1.2%.